Early Anglo-Saxon Christian reliquaries - Gibson, Anthony (Archaeopress Archaeology, 2022)
This volume presents a corpus and discussion of seventy-one Anglo-Saxon copper-alloy containers from forty-nine sites across England dating to the seventh and possibly eighth centuries, and variously described as work boxes, needle cases, amulet containers or Christian reliquaries.